The comparison between novel reagent H-142, H-143, H-145 and xanthate for flotation behaviour of molybdenum-containing ores - Zolzaya, Z; Burmaa, G; Enkhtuul, S; Khasbaatar, D; Munkhshur, M; Otgonjargal, E (Mongolian Journal of Chemistry, 2014)
DOI: http://dx.doi.org/10.5564/mjc.v13i0.160 Mongolian Journal of Chemistry Vol.13 2012: 46-48